CTAB assisted sol-gel synthesis and characterization of FeWO4 and CoWO4 nanoparticles. Issue 10 (2nd October 2020) - Moorthy, Arjun; Bellarmin, V. Robert; Kumaran, Balaji; Saravanan, M. E. Raja
Abstract: Designing sol-gel synthesis of stable oxide nanostructures are one among the few key steps in simplifying the synthesis strategies for mass scale production of such nanomaterials. Herein, low temperature, CTAB based sol-gel technique has been adopted for the development of iron and cobalt tungstate nanostructures as they are one among the potential oxide nanostructures. As synthesized nanoparticles possess fine particle size in polycrystalline nature with good thermal stability and magnetic properties. The procedure adopted produced near-pure materials with no noticeable binary oxide formation and other impurities. These results may lead to promising applications